2016
DOI: 10.1093/infdis/jiw440
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of T-Helper Type 1 (Th1) to Th17 Cytokines in Whole Blood Is Associated With Human β-Defensin 3 Expression in Skin and PersistentStaphylococcus aureusNasal Carriage

Abstract: A low Th1 to Th17 mRNA ratio increases the propensity for persistent S. aureus nasal colonization, with downregulated hBD-3 transcription providing a potential link.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…These were IL-4/IFN-␥ (indicator of Th2/Th1 balance) and IL-4/TNF-␣ (indicator of Th2 response/proinflammatory innate immune response). This approach has been extensively used in previous studies to determine the balance between anti-inflammatory and proinflammatory responses triggered by different stimuli (47)(48)(49). IL-4 was primarily considered as anti-inflammatory cytokine instead of IL-10 since IL-10 production is under the control of IL-4 (50-52).…”
Section: Methodsmentioning
confidence: 99%
“…These were IL-4/IFN-␥ (indicator of Th2/Th1 balance) and IL-4/TNF-␣ (indicator of Th2 response/proinflammatory innate immune response). This approach has been extensively used in previous studies to determine the balance between anti-inflammatory and proinflammatory responses triggered by different stimuli (47)(48)(49). IL-4 was primarily considered as anti-inflammatory cytokine instead of IL-10 since IL-10 production is under the control of IL-4 (50-52).…”
Section: Methodsmentioning
confidence: 99%
“…This was surprising and the authors suggested that IL-17 could be insoluble in nasal secretions ( Cole et al, 2016 ). Low Th1 to Th17 cytokines ratio were found to be predictive of S. aureus carriage in volunteers after whole blood stimulation with S. aureus ( Nurjadi et al, 2016 ). Future human studies should be conducted to better understand the role of Th17 cytokines in nasal carriage.…”
Section: Immune System and S Aureus Colonizationmentioning
confidence: 99%
“…Yet, a differential response to endogenous versus exogenous strains was observed, wherein individuals who carried a persistent strain responded to their endogenous strain with decreased IL-17, but not IFN-␥, levels. The lack of a differential IFN-␥ response is interesting, considering that Nurjadi et al found a significant difference in IFN-␥ mRNA expression between carriers and noncarriers (27). However, the model used by that group was looking at responses to one strain (essentially representing all strains) and not individual carried strains.…”
Section: Discussionmentioning
confidence: 99%
“…Nurjadi et al tested cytokine expression levels in persistent S. aureus carriers and noncarriers. They observed no difference in IL-17 mRNA expression between carriers and noncarriers but did observe a difference in gamma interferon (IFN-␥) expression between carriers and noncarriers and concluded that the ratio of IFN-␥ to IL-17 could be used to predict carriage (27).…”
mentioning
confidence: 99%